Wisdom Of Zakat (Muzakki Behavioral Phenomenon Of Paying Zakat For Professionals In Langsa City, Aceh Province): bahasa - Safwan Kamal Safwan (Maro: Jurnal Ekonomi Syariah dan Bisnis, 2021)
Zakat is defined as one of the pillars of Islam, however the presence of professional zakat that has developed in contemporary times, nowadays has received various responses from the community. This paper aims to analyze how the behavior of people in Langsa City in paying professional zakat. this study also tries to elaborate the wisdom felt by the community while consistently paying professional zakat. Method used in writing this research is a qualitative which based on field research. A phenomenological approach is employed to unravel the wisdom of zakat felt by muzakki. This study involved 5 (five) informants with interview and documentation data sources approachs. This study found that the behavior of muzakki in paying professional zakat is reflected in the theory of planned behavior which includes attitudes, subjective norms as well as behavioral control. In terms of the attitude; the behavior of muzakki in paying zakat is driven by psychological wisdom, social wisdom, economic wisdom and biological wisdom. Moreover, in regards to subjective norms, the behavior of muzakki in paying professional zakat is encouraged by several media including families, educational institutions, through online information, government regulations and organizations. In terms of behavioral control, muzakki pay zakat since there are systems provided for paying zakat systematically, manually, as well as online.